Early Trauma and Cognitive Functions of Patients With Schizophrenia - Carrilho, Carolina G.; Cougo, Simone S.; Bombassaro, Tatiane; Varella, André Augusto B.; Alves, Gilberto S.; Machado, Sergio; Murillo-Rodriguez, Eric; Malaspina, Dolores; Nardi, Antonio E.; Veras, André B. (Frontiers in Psychiatry, 2019)
Aim: The following work aims at investigating the putative relation between early psychological trauma, cognitive functioning and psychotic symptoms in individuals diagnosed with schizophrenia. Methods: A quantitative assessment was performed with 20 individuals diagnosed with schizophrenia according to DSM-5 criteria, who were being treated in Psychosocial Community Care Centers in Brazil. Clinical measurements comprised a semi-structured clinical interview, a screening questionnaire for common mental disorders, the Positive and Negative Syndrome Scale (PANSS) and the Early Trauma Inventory - Short Form (ETISR-SF); Cognitive assessment included Beta III test, Concentrated Attention (CA) test, Color Trails Test (CTT), Visual Face Memory (VFM) test. Results: age-adjusted analysis showed a negative correlation between early trauma and visual memory performance (r= -.585, p=.007) and negative symptoms and attention performance (r= -.715, p=.000). Conclusion: Although cause-effects relation cannot be firmly stated, an association between early trauma experience and later cognitive impairment, particularly in visual memory and attention domains, is suggested by our preliminary findings. Future studies with larger sample size and prospective design will clarify the long-term effects of early exposure to trauma and its clinical meaning in terms of developing psychotic related illness.